Impact of piscivorous fish introduction on fish communities of small temperate lakes in Gatineau Park, Quebec, Canada - Aiken, James (University of Ottawa (Canada), 2009)
Small temperate lakes are under increasing pressure from a number of anthropogenic sources, including but not limited to: habitat alteration, invasive species, climate change, and pollution. In Gatineau Park, Quebec, Canada small temperate lakes have been demonstrated to be under threat from introduced piscivores, among other potential stressors. Here, I assessed the historical impact of four introduced piscivores on minnow, small fish and total fish species richness for a set of small Gatineau Park lakes. Fish community data were obtained from two previously published studies and a lake survey conducted in the summers of 2006 and 2007. I used a modified Control/Impact study design and repeated measures analysis of variance to test the hypothesis that introduced piscivores negatively affect species richness over time. My results strongly demonstrate that piscivores have had a negative effect on minnow and small fish species richness over time, whereas total fish species richness was unaffected. Assuming that these introduced piscivores pose a risk to the parks small temeprate lakes, I then assessed what lake characteristics best predict piscivore invasion risk. To do this, I estimated invasion risk employing two different analytical approaches for a total of 42 small lakes located in Gatineau Park using current and historical data collected in 1971, 1981, 1991 and 2006. Bootstrapped logistic regression was used to predict historical occurrence, and whether or not a lake was invaded/not invaded over time using predictor variables that included lake anthropogenic, spatial-isolation, and morphometric factors. For both logistic regression analyses, lake area and small fish species richness were found to be excellent predictors of piscivore invasion risk and historical occurrence, while lake spatial-isolation factors were also found to be excellent predictors of piscivore historical occurrence. The bootstrapped models with the most support based on Akaike's Information Criterion corrected for small sample size (AICc) were then used to identify lakes at greatest risk for future invasion. My results support the contention that introducing top predators into novel aquatic environments has detrimental impacts on native fish communities, and that these impacts are not always immediately obvious, but are indeed discernable over time. In conclusion, I make specific recommendations to guide the conservation and management of small temperate lake ecosystems.
Keywords: Biology, Ecology.; Biology, Limnology.